Mapping Primary School Leadership in a Post-Conflict Context : The Case of Timor-Leste. - Ribeiro, Shayla Maria Babo (Cambridge Scholars Publisher, 2020)
This book focuses on primary school leadership in the post-conflict and developing country of Timor-Leste. In doing so, it reports on research that has charted a 'narrative arc' comprising the historical background to primary school leadership, as well as the current concerns perceived by primary school leaders and the strategies they adopt when dealing with the challenges encountered in their day-to-day work. This exposition reveals the significant progress that has been made in establishing a universal, mandatory, and free Basic Education system during the country's emergence as a post-confl.
Description based upon print version of record.
Keywords: Educational leadership -- Timor-Leste.; Elementary school administration -- Timor-Leste.; War and education -- Timor-Leste.; Leadership en éducation -- Timor oriental.; Écoles primaires -- Timor oriental -- Administration.; Éducation et guerre -- Timor oriental.; Education.; Management: leadership & motivation.; Educational strategies & policy.; Educational leadership; Elementary school administration; War and education; Timor-Leste